2012
DOI: 10.1074/jbc.m112.405787
|View full text |Cite
|
Sign up to set email alerts
|

Novel Activation of Voltage-gated K+ Channels by Sevoflurane

Abstract: Background: Halogenated inhaled anesthetics modulate voltage-gated ion channels by unknown mechanisms. Results: Biophysical analyses revealed novel activation of K v channels by the inhaled anesthetic sevoflurane. Conclusion: K v channel activation by sevoflurane results from the positive allosteric modulation of activation gating. Significance: The unique activation of K v channels by sevoflurane demonstrates novel anesthetic specificity and offers new insights into allosteric modulation of channel gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 42 publications
8
50
1
Order By: Relevance
“…AziSEVO photolabeling of the b 3 -subunit, b 3 -M1 259 W241 and b 3 -M2 29 A249, again supports this a+/b2 interfacial binding cavity. By using mutagenesis and electrophysiology, other investigators have suggested that SEVO and ISO iso have different binding sites in a variety of potassium channels (22,26,49,50), and our results confirm that this is also true in GABA A receptors. Although comparatively less than ISO, a decrease in SEVO-positive modulation was observed within in vitro studies using a 1 -M2 159 S270W or S270I GABA A receptor mutants (8).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…AziSEVO photolabeling of the b 3 -subunit, b 3 -M1 259 W241 and b 3 -M2 29 A249, again supports this a+/b2 interfacial binding cavity. By using mutagenesis and electrophysiology, other investigators have suggested that SEVO and ISO iso have different binding sites in a variety of potassium channels (22,26,49,50), and our results confirm that this is also true in GABA A receptors. Although comparatively less than ISO, a decrease in SEVO-positive modulation was observed within in vitro studies using a 1 -M2 159 S270W or S270I GABA A receptor mutants (8).…”
Section: Discussionsupporting
confidence: 88%
“…All spectra are provided in Supplemental Figs. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Photolabeled residues and their locations within either receptor are displayed in Table 2.…”
Section: Results a 1 B 3 G 2l Gaba A Receptor Electrophysiology With mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has demonstrated that sevoflurane at 1 mM modestly increases the maximal conductance of hKv1.5 channels and shifts the voltage dependence of activation toward more hyperpolarized potentials, through mechanisms involving a positive allosteric modulation of channel gating (Barber et al, 2012). In contrast, propofol blocks the hKv1.5 current with an IC 50 of 49.3 M (Fig.…”
mentioning
confidence: 94%
“…Pipette solution contained (in mM): 15 NaCl, 80 CsF, 40 CsCl, 10 EGTA, and 10 Hepes, pH 7.3 adjusted with CsOH. Sevoflurane containing external solution was prepared by sonication and delivered by a gastight perfusion system as previously described (52). To eliminate inaccuracies caused by membrane lipid retention of anesthetic molecules, each cell was exposed to only one dose of anesthetic agent and washout data were not used.…”
Section: Methodsmentioning
confidence: 99%